PENGARUH KEPRIBADIAN GURU PAI TERHADAP HASIL BELAJAR SISWA DI SEKOLAH - Suardi M (Institut Agama Islam Negeri Palopo, 2018)
This study aims to determine how the influence of PAI teacher's personality on student learning outcomes in SMA 10 Bulukumba. The approach taken in this study is qualitative research using data collection methods through field research by means of observation and interviews. The data obtained is processed and analyzed through three channels, namely data reduction, data display (presentation) and data verification. The results of the study found that student learning outcomes themselves are influenced by several important factors and it is the responsibility of the teacher to make it happen like motivation, a motivation arises only if because there is a desire to succeed in learning, therefore the personality of a PAI teacher will greatly influence students in learning so that it can improve learning outcomes. Because the personality of a teacher, especially PAI teachers, has a direct and cumulative influence on life and learning habits of students. Students will absorb attitudes, reflect feelings, imitate behavior and cite the teacher's statements. Experience shows that problems related to motivation, discipline, social behavior, achievement and learning desire are derived from the teacher's personality